(untitled) (TUTA Journal, 2024)
In this paper, we study about nuclear spaces of continuous functions and find a new example of nuclear spaces of continuous functions which help us for better understanding of the nuclear spaces of continuous functions. We show that the space of infinitely differential functions on an open set in R2 is nuclear.